Effect of soil nutrients on the stability of superabsorbent polymers as a tool for climate change mitigation - Vavrincová, Lenka; Adamcová, Vanda; Machalová, Linda; Valica, Martin; Rezbárik, Šimon; Horník, Miroslav (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2025)
The aim of this study was to assess the effect of soil nutrients on the stability of superabsorbent polymers (SAPs). In agriculture, SAPs are known to increase productivity in arid regions by improving plant water availability, optimizing root nutrient uptake, and increasing plant drought tolerance. In this study, we tested SAPs derived from starch and mixtures of acrylic acid and acrylamide. First, a physicochemical characterization of the SAPs was performed, which included optimizing the water absorption volume, determining the maximum absorption capacity, and analyzing the water binding kinetics. We then also investigated the effects of elements, such as Na, K, Zn and Cu, on the stability of SAPs. The results showed that the SAPs exhibited a high-water absorption capacity. However, reduced swelling capacity was observed in the presence of Hoagland’s medium and solutions of metal ions (Na, K, Zn, Cu) with equimolar concentrations to potassium in the SAP.